Wind and solar power systems : design, analysis, and operation. - Patel, Mukund R., ....- (Boca Raton : Taylor and Francis, 2006)
Wind and solar energy are pollution-free sources of abundant power. The recent technological breakthroughs have made them highly competitive with conventional coal and nuclear power, and organizations in Europe, Africa, India, China, and South America are all building utility-scale wind and solar power plants. Since publication of the first edition of Wind and Solar Power Systems, this industry has continued to boom, making this update necessary. With reorganization and the inclusion of new chapters and sub-chapters that describe new technologies developed during the last five years, the second edition will continue to provide a quick update on the cutting-edge technology of renewable power systems.
Keywords: Windturbines; Zonne-energie elektriciteitsvoorzieningen